Comparative evaluation of different valerian (Valeriana officinalis L.) lines - Sárosi, Sz.; Tulok, M.; Ferenczy, A.; Repcák, M. (International Journal of Horticultural Science, 2005)
Research project to establish a Hungarian valerian cultivar with acceptable production, biological and chemical properties of five promising Valeriana officinalis L. lines were studied. The populations were not homogeneous especially with regard to leaf shape and colour. Line 'IV/1' showed the strongest vigour, was characterised by the highest root-yield (381.79 g/plant), volatile-oil (0.60 m1/100 g) and valtrat content (1.15%). However, the highest valeric-acid content (0.20%) was measured in another line, 'I/5'. According to our results, the above-mentioned lines (1/5', 'IV/1') could be the basic material of breeding work in the future.